2020
DOI: 10.1038/s41438-020-0305-5
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing provides insights into the genetic diversity and domestication of bitter gourd (Momordica spp.)

Abstract: Bitter gourd (Momordica charantia) is a popular cultivated vegetable in Asian and African countries. To reveal the characteristics of the genomic structure, evolutionary trajectory, and genetic basis underlying the domestication of bitter gourd, we performed whole-genome sequencing of the cultivar Dali-11 and the wild small-fruited line TR and resequencing of 187 bitter gourd germplasms from 16 countries. The major gene clusters (Bi clusters) for the biosynthesis of cucurbitane triterpenoids, which confer a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 80 publications
3
75
0
Order By: Relevance
“…Track A denotes the gene density; tracks B to G show the two, three, four, five, six, and seven allele sites, respectively. The unassembled scaffolds or contigs were assigned to MC00 and the data of gene density was cited from a previous report [27]. A to F indicate the two, three, four, five, six, and seven allele sites; "All" indicates the total number of InDels.…”
Section: Identification and Distribution Of Genome-wide Indelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Track A denotes the gene density; tracks B to G show the two, three, four, five, six, and seven allele sites, respectively. The unassembled scaffolds or contigs were assigned to MC00 and the data of gene density was cited from a previous report [27]. A to F indicate the two, three, four, five, six, and seven allele sites; "All" indicates the total number of InDels.…”
Section: Identification and Distribution Of Genome-wide Indelsmentioning
confidence: 99%
“…Genome-wide SSRs markers have been developed for bitter gourd based on the recently published whole genome sequence [25][26][27]; however, no work has been done on InDel identification and marker development to date. In this study, using the Dali-11 genome as a reference, we identified the genome-wide InDels from resequencing data of 61 Chinese bitter gourd accessions [27]. Based on the polymorphic information content (PIC), we selected and designed a set of highly informative, unique InDel markers.…”
Section: Introductionmentioning
confidence: 99%
“…The initial domestication was dated to 6,000 y ago, followed by the separation of further cultivars 800 y ago. A parallel study by Cui et al ( 2 ) (with partly overlapping authorship) instead inferred that wild bitter gourds and the lineage that gave rise to var. muricata and var.…”
mentioning
confidence: 99%
“…No material is illustrated or vouchered in an herbarium, and some accessions (e.g., THMC170) are labeled as wild in the phylogenies but as cultivar in table S5. Cui et al ( 2 ) included 187 accessions from Asia, Africa, and South America, and rooted their phylogeny on two African species. Including African material was important because M. charantia occurs wild in Africa, Madagascar, and India (and naturalized in many tropical regions; refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation